2003
DOI: 10.1046/j.1469-0691.2003.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of inadequate empirical antimicrobial treatment on patients with bloodstream infections in an intensive care unit

Abstract: Almost a quarter of critically ill patients with bloodstream infections were given inadequate empirical antibiotic treatment, but mortality was not higher in the group with inadequate treatment than in the group with adequate treatment. This fact was probably due to microbiological factors and clinical features, such as the type of microorganism most frequently isolated and the source of the bacteremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(111 citation statements)
references
References 34 publications
2
99
0
10
Order By: Relevance
“…Most cases of severe sepsis occur in patients who are already hospitalized for other reasons. In a series of 166 patients with bloodstream infections admitted to an intensive care unit we found that 82.5% of patients had nosocomial acquired infections, and the nosocomial origin of the bacteremia was associated with inadequate empirical antimicrobial treatment (Zaragoza, 2003). Dombrovskiy et al used the NIS to show that from 1993 to 2003, the age-adjusted rate of hospitalization for severe sepsis increased from 66.8 to 132.0 cases per 100,000 persons (Dombrovskiy, 2007).…”
Section: Incidence Of Severe Sepsis and Septic Shockmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of severe sepsis occur in patients who are already hospitalized for other reasons. In a series of 166 patients with bloodstream infections admitted to an intensive care unit we found that 82.5% of patients had nosocomial acquired infections, and the nosocomial origin of the bacteremia was associated with inadequate empirical antimicrobial treatment (Zaragoza, 2003). Dombrovskiy et al used the NIS to show that from 1993 to 2003, the age-adjusted rate of hospitalization for severe sepsis increased from 66.8 to 132.0 cases per 100,000 persons (Dombrovskiy, 2007).…”
Section: Incidence Of Severe Sepsis and Septic Shockmentioning
confidence: 99%
“…In this series the most frequent comorbidities were diabetes (12.2-18,7%), hypertension (7.0-18.6%), cancer (14.5-18.0%) and congestive heart failure (8.6-15.2%). The coexisting conditions represented in observational studies (Zaragoza 2003 andArtero 2010) are probably more representative of those in all patients with severe sepsis and septic shock than are the conditions documented in participants in clinical trials, from which patients with certain medical conditions (e.g., HIV infection, or cancer) may be excluded. In our series of 455 patients with severe sepsis and septic shock admitted to ICU diabetes mellitus was the most prevalent comorbity, followed by chronic heart failure and CPOD (See table 5).…”
Section: Comorbiditiesmentioning
confidence: 99%
“…The earlier appropriate therapy is started, the better the patient's prognosis will be (B). (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) Appropriate antibiotic therapy allows for deescalation from empirical therapy to a more specific antibiotic regimen, which is suitable for organism sensitivity and may prevent the risk of selecting resistant bacteria (D). (17)(18)(19)(20) Antibiotic de-escalation to more specific and less numerous antibiotic regimens reduces the overall cost of therapy (B).…”
Section: Is the Causative Agent Identification Relevant?mentioning
confidence: 99%
“…Additionally, tailoring antibiotic therapy to the organism sensitivity data results in lower mortality (B) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)21,22,(24)(25)(26) (D). (17)(18)(19)(20) Some studies have shown that running blood cultures in patients without risk factors hospitalized for community-acquired pneumonia may not be costeffective given the low rate of positive results (B) (31) (C) (32) .…”
Section: Recommendationmentioning
confidence: 99%
“…There are few reports have described the prevalence of antimicrobial resistance in Kingdom of Saudi Arabia. 18 The problem of antimicrobial resistance in Kingdom of Saudi Arabia is an emerging problem where, the complete elimination of antimicrobial use is not possible due to persistent existence of infectious diseases worldwide and in Saudi Arabia. 9 Therefore, it requires some other alternative.…”
Section: Introductionmentioning
confidence: 99%